Effectiveness of Using English E-Module To Motivate and Improve Students’ English Ability of SMAN 1 Nan Sabaris Padang Pariaman - Yosa Novia; Yenni Rozimela; M. Zaim (INTERNATIONAL JOURNAL OF LANGUAGE PEDAGOGY, 2022)
English has become a core skill that should be mastered by the human resources of a nation in order to be able to compete globally. However, English is still considered by students as a difficult subject to learn. English is still a frightening specter for most students in Indonesia so that students' motivation and learning outcomes are still low. When technology is used wisely and creatively, it may help students become more interested in studying at any time and in any place. As a result the students' motivation in reading and using textbooks will be increased, especially in reading English textbooks. Multimedia technology, for example, has the potential to turn a traditional classroom into a world of infinite imaginary environments. Therefore, it is necessary to use technology-based learning media that can be used by students to increase their motivation and English ability, one of which is the use of e-module. This research is an experimental study with a cross-sectional study design. This research was conducted from July 2021 to March 2022. The application of the e-module was carried out for one semester. The study was conducted at SMAN 1 Nan Sabaris, Padang Pariaman Regency with students and teachers of X class as respondents. The results showed that the use of e-module was effective in increasing the motivation and learning outcomes of the student of X Class of SMAN 1 Nan Sabaris.